Nutritional deficiencies in low-sociodemographic-index countries: a population-based study - Li, Huansong; Ren, Huiming; Guo, Xu; Chen, Zhu (Frontiers in Nutrition, 2023)
Background: We aimed to estimate the burden of nutritional deficiency according to gender in countries with a low sociodemographic index (SDI). Methods: Following the methods of the Global Burden of Diseases, Injuries, and Risk Factors Study 2019, the estimated annual percentage changes (EAPCs) were calculated to determine trends in the age-standardized incidence rate of nutritional deficiency and the associated disability-adjusted life-years (DALYs) and main DALY subcategories from 1990–2019 in low-SDI countries. Findings: From 1990 to 2019, the age-standardized incidence rate and age-standardized DALY rate showed decreasing trends, with EAPCs of -0.90 (95% confidence interval [CI], 1.06 to -0.75) and -3.20 (95% CI, -3.29 to -3.10), respectively, in low-SDI regions. Of the subcategories analyzed, the age-standardized incidence rate of vitamin A deficiency was the highest, and protein–energy malnutrition contributed to the largest age-standardized DALY rate in 2019. From 1990 to 2019, the greatest decrease in the age-standardized incidence rate was observed for vitamin A deficiency, and protein–energy malnutrition showed the greatest decrease in age-standardized DALY rate. At the national level, from 1990 to 2019, the most significant increase in the age-standardized incidence rate for overall nutritional deficiency was observed in males in Afghanistan (EAPC: 0.28 , 0.07 to 0.49). Of the age groups analyzed, the highest incidence rate and DALY rate of overall nutritional deficiency and dietary iron deficiency were observed in children aged 1–4 years. Interpretation: The age-standardized incidence rate and DALY rate decreased significantly from 1990 to 2019, especially for vitamin A deficiency and protein–energy malnutrition. Overall nutritional deficiencies and dietary iron deficiency were mainly concentrated in children aged 1–4 years.